Policy-based commitments in a post-2012 climate framework working paper - Lewis, Joanna (Pew Center on Global Climate Change, 2007)
This paper examines policy-based climate commitments as an element of a post-2012 international climate framework. It is part of a Pew Center series expanding on key recommendations of the Center's Climate dialogue at Pocantico.